Phytochemical characterization of Thevetia peruviana (lucky nut) bark extracts by GC-MS analysis, along with evaluation of its biological activities, and molecular docking study - Rao Anum Rehman Khan; Samina Afzal; Hanan Y. Aati; Sultan Aati; Huma Rao; Saeed Ahmad; Musaddique Hussain; Kashif ur Rehman Khan (Heliyon, 2024)
Thevetia peruviana (T. peruviana; Family: Apocynaceae), commonly known as Lucky Nut, is a traditionally and medicinally important plant, and the barks of the plant are traditionally used as anti-inflammatory, anti-diabetic, and antibacterial remedies. Thus, this study aimed to evaluate bioactive phytochemicals and in-vitro biological activities from the bark of T. peruviana using methanolic (TPM) and dichloromethane (TPD) extracts. The GC-MS analysis showed the presence of 54 and 39 bioactive compounds in TPM and TPD, respectively. The TPM extract has a higher level of total polyphenolic contents (TPC: 70.89 ± 1.08 and 51.07 ± 0.78 mg GAE/g extracts, while TFC: 56.89 ± 1.16 and 44.12 ± 1.76 Qu.E/g extracts for TPM and TPD, respectively). Herein, the results of antioxidant activities were also found in correlation with the total polyphenolic contents i.e., depicting the higher antioxidant potential of TPM compared to TPD. The significant inhibitory activities of extracts were observed against tyrosinase (TPM; 59.43 ± 2.87 %, TPD; 53.43 ± 2.65 %), lipoxygenase (TPM; 77.1 ± 1.2 %, TPD; 59.3 ± 0.1 %), and α-glucosidase (TPM; 71.32 ± 2.44 %, TPD; 67.86 ± 3.011 %). Furthermore, in comparison to co-amoxiclave, the antibacterial property against five bacterial strains was significant assayed. The compounds obtained through GC-MS analysis were subjected to in-silico molecular docking studies, and the phyto-constituents with maximum binding scores were then subjected to ADME analysis. The results of in-silico studies revealed that the binding affinity of several phyto-constituents was even greater than that of the standard inhibitory ligands. ADME analysis showed bioavailability radars of phyto-constituents having maximum docking scores in molecular docking. The results of this study indicated that T. peruviana has bioactive phytochemicals and therapeutic potential and may provide a basis for treating metabolic disorders (inflammatory diseases like rheumatism and diabetes), bacterial infections, and skin-related problems.